Influence of Ethyl Acetate, Isoamyl Acetate and Linalool on off-flavour Perception in Beer - Hanke, Stefan; Ditz, V.; Herrmann, M.; Back, Werner; Becker, Thomas; Krottenthaler, Martin (BrewingScience, 2010)
Beer flavour is a very complex flavour created by interaction off several hundred aroma compounds. Obvious off-flavours which can be detected by the consumer decrease the drinkability and acceptance of a beverage. The image of a brand can be damaged. It is known that undesired flavours, like stale flavour, can be masked by positive ones like certain hop flavours. Therefore it is of interest to find out if other off-flavours can also be masked by positive aroma compounds. Positive flavour impressions are e.g. linalool and some esters among others. Whether these compounds can suppress the perception of dimethyl sulphide (DMS), diacetyl and isovaleric acid in beer is unknown until today. In this study the influence of ethylacetate, isoamyl acetate and linalool on flavour thresholds of DMS, isovaleric acid and diacetyl was investigated. The obtained results show that linalool decreases the perceived intensity of off-flavours at low concentrations but increases at higher concentrations. Esters also showed suppressing and synergistic effects. The flavour composition is an important factor for flavour perception and must be taken into account when comparing flavour thresholds of flavour compounds determined in different beers types.